Antistaphylococcal evaluation of indole–naphthalene hybrid analogs - Ashraf K; Yasrebi K; Adeniyi ET; Hertlein T; Ohlsen K; Lalk M; Erdmann F; Hilgeroth A (Dove Medical Press, 2019)
Kerolos Ashraf,1 Kaveh Yasrebi,1 Emmanuel Tola Adeniyi,2 Tobias Hertlein,2 Knut Ohlsen,2 Michael Lalk,3 Frank Erdmann,1 Andreas Hilgeroth1 1Institute of Pharmacy, Martin Luther University Halle-Wittenberg, Halle, Germany; 2Institute of Molecular Infection Biology, Julius Maximilians University Würzburg, Würzburg, Germany; 3Institute of Biochemistry, Ernst Moritz Arndt University Greifswald, Greifswald, Germany Abstract: Resistance developments against established antibiotics are an emerging problem for antibacterial therapies. Infections with Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) have become more difficult to treat with standard antibiotics that often fail, especially against MRSA. In consequence, novel antibiotics are urgently needed. Antibiotics from natural sources own complicated structures that cause difficulties for a chemical synthetic production. We developed novel small-molecule antibacterials that are easily accessible in a simple one-pot synthesis. The central indolonaphthalene core is substituted with indole residues at various positions. Both the varied indole substitutions and their positions at the molecular scaffold influence the determined antibacterial activity against the evaluated Staphylococcus strains. Best activities have been found for 5-chloro, -cyano, and -hydroxyl indole substitutions. Therefore, first promising lead compounds could be identified that are nontoxic in human HEK and SH-SY5Y cells and exceed the activity of used standard antibiotics, especially against MRSA. Keywords: structure-dependent activity, lead structure, antibacterial activity, compound evaluation, MRSA